Genomic identification of cotton SAC genes branded ovule and stress-related key genes in Gossypium hirsutum - Shuya, Ma; Le, Liu; Huiyun, Shi; Yu, Gu; Yujun, Li; Qanmber, Ghulam (Frontiers in Plant Science, 2023)
SAC genes have been identified to play a variety of biological functions and responses to various stresses. Previously, SAC genes have been recognized in animals and Arabidopsis. For the very first time, we identified 157 SAC genes in eight cotton species including three diploids and five tetraploids with 23 SAC members in G. hirsutum. Evolutionary analysis classified all cotton SAC gene family members into five distinct groups. Cotton SAC genes showed conserved sequence logos and WGD or segmental duplication. Multiple synteny and collinearity analyses revealed gene family expansion and purifying selection pressure during evolution. G. hirsutum SAC genes showed uneven chromosomal distribution, multiple exons/introns, conserved protein motifs, and various growth and stress-related cis-elements. Expression pattern analysis revealed three GhSAC genes (GhSAC3, GhSAC14, and GhSAC20) preferentially expressed in flower, five genes (GhSAC1, GhSAC6, GhSAC9, GhSAC13, and GhSAC18) preferentially expressed in ovule and one gene (GhSAC5) preferentially expressed in fiber. Similarly, abiotic stress treatment verified that GhSAC5 was downregulated under all stresses, GhSAC6 and GhSAC9 were upregulated under NaCl treatment, and GhSAC9 and GhSAC18 were upregulated under PEG and heat treatment respectively. Overall, this study identified key genes related to flower, ovule, and fiber development and important genetic material for breeding cotton under abiotic stress conditions.